A multicenter interventional study aimed to assess the effectiveness of Lavanda aroma in reducing anxiety and pain in patients undergoing PROstatic BIOpsy (LA-BIOPRO): Study protocol - Tatiana Bolgeo; Roberta di Matteo; Denise Gatti; Salvatore Cotroneo; Pietro Ricci; Andrea Di Stasio; Armando Serao; Carmelo Boccafoschi; Antonio Maconi (Archive of Urological Research - Peertechz Publications, 2022)
Background: A prostatic biopsy is a diagnostic test used in cases of suspected prostate cancer. The patient expresses significant levels of anxiety from the very first outpatient visits; anxiety and pain management is essential for a successful outcome of the procedure. Lavender oil is one of the essential oils that is commonly used in aromatherapy to reduce anxiety and pain, its low toxicity and side effects have made it the preferred treatment in complementary medicine. Aim: To assess the 'effectiveness of lavender scent in decreasing the levels of anxiety and pain in patients undergoing a prostatic biopsy. Methods: An interventional non-pharmacological, randomized, two-arm, multi-center, nonprofit study. The SS Antonio e Biagio e Cesare Arrigo Hospital and the City of Alessandria Clinic, Monza Polyclinic of Alessandria, will enroll consecutively all adult patients undergoing outpatient prostatic biopsy from April 1, 2022, to October 1, 2022. The Numerical Rating Scale and Hamilton Anxiety Rating Scale will be used for assessments. Conclusion: Lavender oil aromatherapy could have a clinically significant effect on reducing pain and anxiety during prostatic biopsy procedures; its simple use, safety, and low cost provide a therapeutic option to be considered, complementary to other medical interventions in certain clinical settings.